The Philosophy of Science, Scientist Responsibilities, and Functional Analysis from an Islamic Perspective - Nurmila Nurmila; Warul Walidin (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: The responsibility of scientists holds deep significance in the Islamic worldview, where responsibility is seen as human awareness of one's behavior and actions, whether intentional or not. Within this framework, Muslim scientists bear a broader moral and spiritual obligation beyond their professional duties. Objective: This study aims to explore and synthesize the concept of scientific responsibility from an Islamic perspective, highlighting how religious teachings shape the ethical and social obligations of Muslim scientists. Method: The study adopts a qualitative approach through thematic analysis of classical Islamic texts, scholarly interpretations, and the views of contemporary Islamic scholars, particularly focusing on the framework proposed by Dr. Yusuf Al-Qaradhawi. Result: The findings indicate that the responsibility of a Muslim scientist includes seven core elements: preserving knowledge, pursuing its depth and essence, applying it in practice, teaching it, publishing and disseminating it, preparing future generations, and dedicating all knowledge and actions to Allah alone. These elements reflect an integrated responsibility that binds scientific endeavor with religious and ethical accountability. Conclusion: The responsibilities of Muslim scientists go beyond secular academic standards, calling for the integration of faith, knowledge, and moral responsibility as a way to uphold the Islamic mission of mercy to all creation (rahmatan lil ‘alamin). Contribution: This study contributes to the discourse on Islamic ethics in science by offering a synthesized framework of responsibilities grounded in Islamic teachings. It provides guidance for Muslim scholars and educators in shaping a science that is both spiritually conscious and socially responsible.